Motor control system development using microcontroller based on PID controller - Abdul Wahab, Siti Nur Wahidah (2014)
PID controllers which are one of the algorithms that can adjust the input values based on historical data and the emergence rate of differences, in order to make the system more accurate and stable. This project is focused mainly on designing and implementing PID controller for a Dc servo motor. The PID controller are used to control position of the Dc servo motor, while the speed motor are control by manually run with a specified performance requirement. PID controller are designed based on MATLAB/Simulink software to obtain the optimum position control of PID controller parameters and realized by using microcontroller to the real Dc servo motor. All codes in microcontroller are developed on MPLAB X IDE software program for embedded system.